The phenomenon of place in the poetry contrasts: ﻇﺎﻫﺮﺓ ﺍﻟﻤﻜﺎﻥ ﻓﻲ ﺷﻌﺮ ﺍﻟﻨﻘﺎﺋﺾ - Shahida, Dr. Salma; Ullah, Dr. Hayat (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
The majority of literary genres in prose are related to the pledge of time and place, so the narration is linked to a specific time in which the events take place within the coordinates of a place, it may be confined to a house or an alley, and it may expand to include different cities, villages and countries, the importance of place in the literary genres could be understand from being an active element in the literary template as it directly affects the representations of the characters of the literary work, and adds an aura of its color to the path of their lives, thus the artistic image of the literary work becomes completed. Place / site in the language has several meanings, including what came in Al-Ain: Site is a place for the being of a thin in it, Abu Mansur said (place and position are in the same meaning). The place is the dwelling containing anything. We also know that the concept of the word (place) has been associated with the location in which people and others spend their lives. In the light of this concept, the Arab sources unanimously agreed that the locus and the plural are places, as mentioned previously. Contradictions: the collection of an antithesis of the invalidation in the construction, which is the demolition, and in the rope, meaning its dissolution, and in the covenant in the sense of not concluding it, the contradiction literally means: to speak in a way that contradicts its meaning, that is, contradicts, and contradicts it in something contradictory or disagrees with it. The antithesis in poetry is for a poet to say a poem in which he speaks to another poet, who obeys him and his people, and is proud of himself and his righteousness, then the other poet answers him with a poem, contradicting what the first came with - or more of the meanings and pictures he brought, adding to it from his side more pride and spelling all That is with the intent to spoil the meaning of the first or explain it to his own interest or the interest of his tribe, and the second poet may go beyond the response to the words of the first and contradict it in the same meaning to general spelling and public pride, then the revocation takes place on the basis of the contrast between satire, satire, pride and pride and in any case the poem of the other poet does not acquire the name Contradiction unless he adheres to the subject that the first poet dealt with by weight and rhyme on which he built his poem, and the first is called antithesis in the sense of contradictory, meaning that the first - in the order of saying - is a subject, in the sense of an operative, and the second is an antithesis in the sense of a contradictory one, so it is verbal, in the sense of an actor. The creative attitude between the two poets, in terms of freedom to choose the subject, weight, rhyme, meanings and emotional gathering.